Factors affecting green purchase intention among university students - Lim, Rui Wen (2023)
The swift growth of the economy and technological advancements in recent decades have undoubtedly enhanced the convenience of people's lives. Nonetheless, these progressions have also given rise to various environmental issues, including pollution, global warming, and climate change. As as result, more and more people are aware about the environmental issues. These people included the business. Numerous businesses are conscious of environmental concerns and aim to play a role in safeguarding the environment. Consequently, they are introducing a range of innovative products designed to exert a lesser impact on the environment compared to conventional products, these are commonly referred to as green products.